The analysis of programming competency in test driven development - Yahya, Norzariyah; Awang Abu Bakar, Normi Sham (The Institute of Electrical and Electronics Engineers, Inc., 2015)
Agile development consist of method such as eXtreme Programming and Scrum. Agile was formalized in 2001 by a group of software development practitioners. Agile is not a tool or a single methodology but it is a philosophy. Test driven development or test first approach is one of the approaches in Agile. Test first is a development process with the implementation of test cases before production code. The objective of this research are twofold; one is to study the implementation of test first over test last in Malaysian education domain, two is to investigate the effects of the differences in programming competency on product quality in test driven development. Experiment results indicated that high and moderate programming competency with test first approach produced low code complexity and coupling between object (CBO) for test first was better for all programming competency. However, test last for low and mixed competency produced more lines of code (LOC). In addition, the lack of cohesion in methods (LCOM) results for all programming competency were varied.